The Effect of Digital Marketing Communication Tools in the Creation Brand Awareness By Housing Companies - Cizmeci, Fusun; Ercan, Tugce (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
Creating brand awareness is the first and most important stage of marketing communication. Many types of marketing communication tools have been used to do this in business processes. Digital marketing tools are actually a deconstruction of traditional marketing tools and have become more important by providing interactivity to both consumers and producers in the marketing process. These tools incorporate consumers into the marketing process as an active, rather than passive, player. For housing companies, systematic and strategic use of digital marketing tools is an important resource in gaining competitive advantage, yet there is limited research on this topic in the literature. In this context, this study made use of the Delphi Method to investigate the impact of digital marketing tools on brand awareness generation among housing companies. Normative inferences were made through interviews with panel participants working in large-scale housing companies, and a theoretical framework was drawn up for usage trends among digital marketing tools. The Delphi results indicated that, in housing companies, marketing tools that create paid digital content (corporate web site, search engine pages, e-mail communication, etc.) currently have a greater impact than those which create proactive content (social media, etc.). However, another significant finding on which there was consensus among the panel participants is that in the creation of brand awareness, digital marketing tools such as Facebook or Twitter which create the latter content will become more important in the future.
Keywords: Delphi analysis technique; digital marketing communication; digital marketing communication tools; brand awareness; Architecture